Fly-ash derived crystalline Si (cSi) Improves the capacity and energy density of LiNi0.8Co0.1Mn0.1O2 battery: Synthesis and performance - Cornelius Satria Yudha; Windhu Griyasti Suci; Enni Apriliyani; Agus Purwanto; Yuli Yetri; Rusdianasari (Results in Engineering)
For decades, graphite has been the key ingredient in the anode of Li-ion batteries (LIBs). The search for high-capacity anode materials for Li-ion batteries (LIBs) has led to increasing interest in silicon (Si) as a potential replacement for graphite. This study presents an innovative approach to synthesizing crystalline Si (cSi) from type C fly ash, addressing both the need for improved LIB anodes and the challenge of industrial waste management. Our novel process involves a stepwise method of extraction, gelation using various mineral acids (HCl, H2SO4, and HNO3), magnesiothermic reduction, and purification. X-ray diffraction and energy-dispersive X-ray spectroscopy confirmed the production of high-purity SiO2 and cSi. Notably, a cSi-doped graphite anode (5 % Si) paired with LiNi0.8Mn0.1Co0.1O2 (NMC811) in a cylindrical cell achieved a minimum specific discharge capacity of 388 mAh/ganode after formation, surpassing the theoretical capacity of graphite (372 mAh/g). This demonstrates that even a small amount of cSi can significantly enhance anode performance. Our scalable, simple, and economical process offers a dual benefit: improving battery characteristics while providing an efficient method for fly ash waste utilization. This approach paves the way for sustainable production of high-performance LIB anodes while addressing critical waste management challenges.